Rejoinder to Block on indifference - Wysocki, Igor (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
This paper is a rejoinder to Block’s (2022) response to Wysocki’s (Wysocki, 2021) essay on Nozick’s challenge leveled at Austrian economics. Instead of merely reiterating Wysocki’s (Wysocki, 2021) position, we try to highlight that the Blockean account of indifference and preference entails the views which are otherwise unwelcome, given his unyielding commitment to Austrian economics at large. To wit, we argue that Block’s theory still fails to make sense of the law of diminishing marginal utility. Moreover, his extreme idea of choice, sadly, appears to jettison characteristically Austrian subjectivism and thus perilously verges on behaviourism. We conclude that, given all these predicaments the Blockean account is caught in, Block himself (qua Austrian) has a reason to embrace the Hoppean theory of preference and indifference.
Keywords: choice; indifference; preference; Hans-Hermann Hoppe; Walter Block